Analisis Program Corporate Social Responsibility (CSR) BUMN dalam Peningkatan Kinerja UMK di Kota Bengkulu - Bertha Iin Esti Indraswanti (Universitas Bengkulu, 2026)
ABSTRACT The purpose of this research was to analyse the CSR Programme of public entreprise on Bengkulu MSEs. The analyse method is descriptive analysis which based on primary data. Data was taken from 5 BUMN and 21 MSEs of their partner. There are two models MSEs empowerment from CSR Programmes. There are lending model and non lending model. The CSR Programmes improve the MSEs capacity. It can increase the variation of product (product diversification), volume of production, sales, profit and market capture. The non lending model programme more effective than the lending model. The lending model has high non loan. So, since 2025, three BUMN change their policy. Two of them make a partnership with bank to recruitment MSEs, and one BUMN make a decision by prerequisite involved training. Keywords: CSR, Micro Small Enterprises.